The Effect of a Combination of Brisk Walking Exercise and Bay Leaf Decoction on Changes in Blood Sugar Levels in Diabetes Mellitus Patients - Badriah, Siti; Permana, Ridwan Chandra; Adini, Syaukia; Kustiawan, Ridwan; Somantri, Iwan (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Diabetes mellitus is a clinical condition of metabolic disease characterized by an increase in blood sugar levels or called hyperglycemia due to failure of insulin secretion, insulin performance or both. Management of diabetes mellitus can be helped non-pharmacologically in the form of brisk walking exercises and boiled bay leaves. This research aims to determine the effect of a combination of brisk walking exercise and boiled bay leaves on reducing blood sugar levels in people with type 2 diabetes mellitus. This type of research is quasi-experimental with pretest - posttest with control group. The instruments used were an observation sheet and a glucometer set. Sampling used probability sampling with purposive sampling consisting of 38 respondents for the intervention group and 38 respondents for the control group. The data analysis used was the Wilcoxon test and the Mann-Whitney test. The results showed a significant reduction in blood sugar levels in the intervention and control groups. However, there was a significant reduction in blood sugar levels in the intervention group with a p-value of 0.000. This study concluded that there was an effect of the combination of brisk walking exercise and boiled bay leaves on reducing blood sugar levels in people with type 2 diabetes mellitus.